PEMBUATAN MEDIA PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI SMA MASEHI GBKP BRASTAGI, KABUPATEN KARO - Surianto Sitepu; Jimmy Febrynus Naibaho; Naikson Fandier Saragih; Samuel Van Basten Manurung; Indra Kelana Jaya; Alfonsus Situmorang; Imelda Sri Dumayanti; Asaziduhu Gea; Benget Rumahorbo; Marzuki Sinambela; Yolanda Yulianti Pratiwi Rumapea; Margaretha Yohanna; Harlen Gilbert Simanullang; Dandi Daniel Siregar (Universitas Methodist Indonesia, 2021)
Learning that uses electronic services as a tool is known in general as e-learning or LMS (Learning Management System). Training on e-learning is realized in Community Service Activities (PKM) as the implementation of the Tri Dharma of Higher Education as well as sharing and contributing ideas and transferring knowledge and technology for teachers and students at SMA Masehi GBKP, Brastagi. This service activity was carried out for a day, with material on Making Online Learning Media during the COVID-19 Pandemic. The material for the activities carried out included making online learning media using Edmodo and Easy Class. The online learning media is one of the effective solutions to facilitate online teaching and learning activities for teachers and students. His presence, which is increasingly easy to find, certainly helps teachers and students stay safe studying at home, without being limited by place and time.